EMC research of 18-pulse circuit consisting of 3L-NPC converters with SHE - Maklakov, A. S.; Demov, M. A.; Maklakova, E. A.; Gasiyarov, V. R.; Voronin, S. S. (2016 2nd International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2016)
The article deals EMC research of 18-pulse circuit consisting of three level neutral point clamped (3L-NPC) converters with selective harmonic elimination (SHE) algorithm. Main object of research is power circuit of wind-driven electric plants based on 18-pulse circuit consisting of three 3L back-to-back (BtB) converters. A review of contemporary condition of power electronics for application in wind generator systems is presented in the article. THD analysis of voltage and current waveforms has been presented to assessed EMC of the researched power circuit of wind-driven electric plants.